miR-20a Overexpression in Adipose-Derived Mesenchymal Stem Cells Promotes Therapeutic Efficacy in Murine Lupus Nephritis by Regulating Autophagy - Shanshan Wei; Zhiwen Zhang; Lu Yan; Yinjuan Mo; Xianwen Qiu; Xiangbin Mi; Kuan Lai (Stem Cells International)
Objective. Lupus nephritis is the most common and severe complication of systemic lupus erythematosus. The aim of our study was to investigate the efficacy of miR-20a overexpressing adipose-derived stem cell (ADSC) transplantation in murine lupus nephritis (LN) and explore potential molecular mechanisms. Methods. Mouse ADSCs were transfected with a miR-20a lentiviral vector to obtain miR-20a overexpression ADSCs (miR-20a-ADSCs). We first observed the influence of miR-20a on ADSC viability and apoptosis in vitro. B6.MRL/lpr mice were administered ADSC/miR-20a-ADSC intravenously every week from age 30 to 33 weeks, and the lupus and normal control groups received PBS on the same schedule. Results. miR-20a expression increased in miR-20a-ADSC-derived exosomes, and miR-20a overexpression promoted ADSC proliferation and inhibited apoptosis. Compared with ADSCs, miR-20a-ADSC treatment significantly improved serologic and histologic abnormalities, as evidenced by reduced serum creatinine, anti-dsDNA antibody, 24 h urine protein levels, nephritis scores, and C3/IgG deposits. Furthermore, miR-20a-ADSC treatment resulted in downregulated Akt, mTOR, and p62 expression and upregulated miR-20a, Beclin 1, and LC3 II/I expression compared with ADSC treatment. After treatment with miR-20a-ADSC, a significant increase in the number of autophagosomes within podocytes was observed, along with upregulated expression of podocin and nephrin, compared with the ADSC group. Conclusions. miR-20a-ADSC transplantation prevents the development of lupus nephritis and significantly ameliorates already-established disease, and its mechanism is related to autophagy by targeting the miR-20a-regulated mTOR pathway.